Construction logistics governing guidelines in urban development projects. Issue 1 (12th February 2019) - Janné, Mats; Fredriksson, Anna
Abstract : Purpose: Although a construction logistics solution is necessary for dealing with the demands in many large urban development projects, there is a lack of research on governance mechanisms for construction logistics solutions. Therefore, the purpose of this paper is to analyse the initiation and utilisation of a construction logistics centre (CLC) from different stakeholders' perspectives to suggest governance mechanisms for strategic, tactical and operational levels and to develop guidelines for implementing these governance mechanisms. Design/methodology/approach: A single case research design was used. Data were collected through interviews, site visits, observations and documentation from four stakeholder groups. Findings: There is potential for utilising CLCs in development projects, with positive effects such as consolidation effects and enhanced planning. What is evident, however, is that the design and implementation of the CLCs must be based on a comprehensive stakeholder analysis, as there are conflicting goals between stakeholders. Governance mechanisms, including flexibility in the main contractors' working construction process, as well as clearly stated roles, responsibilities and communication must be developed to enhance this potential. Research limitations/implications: The conflicting goals of CLCs are identified and discussed, and the results show the need for further multi-stakeholder analysis of construction logistics solutions. Practical implications: The experiences from the studied case are developed into practical guidelines to be used in the design of construction logistics solutions in development projects. Originality/value: This study contributes by taking a multi-stakeholder perspective on CLCs and providing guidelines to be used in the design of construction logistics solutions in development projects.